Alih Aksara dan Alih Bahasa Teks Hikayat Maharaja Ali - Indah Widya Sari; Nurizzati; Muhammad Adek (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
This study aims to describe, translate and translate the classic manuscript text entitled Hikayat Maharaja Ali. This research is included in philological research because it aims to understand the texts of ancient manuscripts and thus allow further interpretation and use of these texts based on this understanding. The object of philological research is ancient texts and manuscripts. The method used is the philological method based on the phylological research stages. At the data collection stage, the literature study method was used; descriptive method is used at the description stage of the manuscript; at the script transfer stage, the script transfer method is used; at the translation stage, the translation method is used. The result of the research is a description of information about the Hikayat Maharaja Ali manuscript, the transcription form of the Hikayat Maharaja Ali script in Latin script, and the translation form of the Hikayat Maharaja Ali script in Indonesian.